Mispronouncing English Vowel Sounds on Office Administrative's Students Universitas Bina Sarana Informatika - Ary Iswanto Wibowo; Wiruma Titian Adi; Rizky Mirana Desi Pratama (Universitas Musamus Merauke, 2022)
The objective of this research is to figure out the mispronouncing english vowel sounds that is mostly made by University Students. The data were from 30 students of Office-Administration Study Program Universitas Bina Sarana Informatika as the object of this research. Qualitative method is used for analyzing the recorded sounds that were produced by the students. The vowel sounds investigated in this research were sound of [É‘Ë], [ÉœË], and [á´:]. The researchers gave 7 words each that contain the vowel sounds. The result indicated that mostly students produced the mispronuncing sound [á´:]. They often missed or slip between [É‘Ë] and [á´:]. This happened when the words tested were unfamiliar for the students.